Effective Monitoring as a Shield Against Financial Statement Fraud: A Case of Overvalued Equity in Indonesian Public Companies - Marsellisa Nindito; Adam Zakaria (Jurnal Dinamika Akuntansi, 2025)
Abstract Purposes: This study investigates how overvalued equity affects the occurrence of financial statement fraud in Indonesia and also examines the need for companies to uphold financial statement integrity effectively.Methods: This study applies a quantitative method to analyze 387 data units from manufacturing companies listed on the Indonesian Stock Exchange (2017 to 2019). The logistic and moderation regression analyses are applied to investigate the roles of effective monitoring, proxied by audit committee and audit tenure, in the research model.Findings: Research results revealed that overvalued equity significantly increases the likelihood of financial statement fraud, and that the audit committee can moderate its impact.Novelty: This study addresses a critical gap in the literature by examining the impact of overvalued equity on financial statement fraud in the Indonesian context. Unlike prior research that focuses on developed markets, this study explores the moderating roles of effective monitoring and provides new insights into its effectiveness in mitigating fraud risks. Furthermore, grounded in agency theory, this research advances our understanding of governance mechanisms in emerging markets and offers practical implications for regulators and corporate governance practices.Keywords: Financial Statement Fraud, Overvalued Equity, Effective Monitoring, Audit Committee, Audit Tenure, Corporate Governance